Aquifer distribution and groundwater geochemistry in Bojonegoro Sub-district, Bojonegoro District, East Java Province, Indonesia - Wahyu Wilopo; Doni Prakasa Eka Putra; Raja Susatio (Journal of Degraded and Mining Lands Management, 2020)
Bojonegoro Sub-district is the capital of Bojonegoro District, East Java Province, Indonesia. This area has quite high economic growth supported by large oil and gas reserves in the district. An increasing number of population and improving economy will cause more water needs. People in this area use groundwater as their main source for daily purposes. However, information on the potential of groundwater resources is not yet well available. Therefore, the study aims to determine groundwater flow patterns, the distribution of aquifers, and groundwater geochemistry. The study was conducted by measuring groundwater level as many as 42 points; both dug wells and deep wells, 18 points geo-electrical surveys, and chemical analysis of eight groundwater samples. The results showed groundwater flow direction into the Bengawan Solo River with the primary aquifer of the sandstone lens. All groundwater samples indicate that the type of groundwater is calcium magnesium bicarbonate (Ca2+ - Mg2+ - HCO3-) and come from one system. High nitrate content was found in some areas, probably due to contamination from agricultural or urban wastewater. Therefore, it needs some actions for groundwater protection and conservation in this area to support the sustainable use of groundwater.